Colorectal Cancer Prevention: How to Screen for Colorectal Cancer and Why 45 Is the New 50 When It Comes to Screening - Melissa J. Vilaro; Valeria Westring; Rebecca M. Elliot (EDIS)
This article is for adults at average risk of getting colorectal cancer. This article is meant to help readers understand primary prevention and risk reduction approaches. Written by Melissa J. Vilaro, Valeria Westring, and Rebecca M. Elliott, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2023.